Subject Recommended Samples: Snowball Sampling. - Isaias, Pedro (IGI Global, 2012)
This paper proposes and describes a new instructional design framework, primarily inspired through a pedagogical benchmark, designated as IPTEACES (Involvement, Preparation, Transmission, Exemplification, Application, Connection, Evaluation and Simulation), conceived to facilitate e-learning by reducing diversity in e-Learning programmes facing a non-homogeneous audience. More specifically, this paper describes the outcome of a case study on the application of IPTEACES framework to the insurance intermediaries’ certification course in Portugal (n = 3726) from 16 different corporations connected with the insurance and banking industry. This paper presents an overview of the IPTEACES framework, a brief description of the universe of students who attended the courses as well as the learning results. The results achieved by this certification course will be subject to a detail analysis of the success indicators (score) through the use of a regression tree via exhaustive CHAID (Chi-squared Automatic Interaction Detector) in order to better comprehend the impact that this framework had among the socio demographic different characteristics. Also, results will be presented in the application of a benchmark methodology proposed by Levy (Assessing the value of e-learning systems. Hershey: Information Science Publishing, 2006) and (Int J Inform Syst Serv Sector 1(1):93–118, 2009) for the assessment of effectiveness of IPTEACES e-Learning framework. This e-Learning project achieved the category of “High effectiveness” (score = 0.757) based on the assessment from 1,317 students on satisfaction and importance of 41 e-Learning system characteristics.